Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.jmb.2007.11.024
|View full text |Cite|
|
Sign up to set email alerts
|

HsdR Subunit of the Type I Restriction-Modification Enzyme EcoR124I: Biophysical Characterisation and Structural Modelling

Abstract: Type I restriction-modification (RM) systems are large, multifunctional enzymes composed of three different subunits. HsdS and HsdM form a complex in which HsdS recognizes the target DNA sequence, and HsdM carries out methylation of adenosine residues. The HsdR subunit, when associated with the HsdS-HsdM complex, translocates DNA in an ATP-dependent process and cleaves unmethylated DNA at a distance of several thousand base-pairs from the recognition site. The molecular mechanism by which these enzymes translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 69 publications
(96 reference statements)
0
31
1
Order By: Relevance
“…It has been known that a complex of HsdS and HsdM recognizes and methylates 5'-GA m6 A(6N)TGCC-3' or 5'-GGC m6 A(6N)TTC-3' (Lee et al, 1997;Obarska-Kosinska et al, 2008). However, our results showed that rHsdM alone had the ability to transfer a methyl group in eukaryotic DNA.…”
contrasting
confidence: 80%
“…It has been known that a complex of HsdS and HsdM recognizes and methylates 5'-GA m6 A(6N)TGCC-3' or 5'-GGC m6 A(6N)TTC-3' (Lee et al, 1997;Obarska-Kosinska et al, 2008). However, our results showed that rHsdM alone had the ability to transfer a methyl group in eukaryotic DNA.…”
contrasting
confidence: 80%
“…In contrast to the situation with type II restriction enzymes, it is only very recently that partial atomic structures for type I RM subunits have emerged (Calisto et al 2005;Kim et al 2005;Obarska et al 2006;Obarska-Kosinska et al 2008;Kennaway et al 2009;Lapkouski et al 2009;Uyen et al 2009;Taylor et al 2010;Gao et al 2011), and their mechanisms, which most dramatically involve the translocation of thousands of base pairs of DNA with the formation of supercoiled loops (Yuan et al1980;Endlich and Linn 1985;Studier and Bandyopadhyay 1988;García and Molineux 1999), still present many questions. The type I RM enzymes are complex structures with two HsdR restriction (R) subunits, two HsdM modification (M) subunits, and one HsdS sequence specificity (S) subunit (Murray 2000;Loenen 2003), each with a number of domains (Supplemental Fig.…”
mentioning
confidence: 99%
“…As demonstrated for a related Type I R-M enzyme EcoKI in partial proteolysis experiments, cleaving off 155 terminal residues of HsdR produced a fragment stable in the presence of ATP but unable to bind to MTase (24). De novo modelling of HsdR from EcoR124 supported the notion of the C-terminus actively participating in complex formation, albeit revealing little about its structural organization except for a relatively short coil-coiled fragment and an overall disordered nature (25). Another known crystal structure of HsdR from Vibrio vulnificus also lacks ~220 C-terminal residues and folds into three domains (endonuclease and two RecA-like helicases), providing no further insight into the 3D structure of the C-terminus.…”
Section: Introductionmentioning
confidence: 84%
“…Within the Type IC family, full sequences are only available for EcoR124 and NgoAV from Neisseria gonorrhoeae (27) that display ~75% sequence identity. An alignment between members of different families was nevertheless achieved in endonuclease and helicase I and II domains due to the presence of clearly defined motifs (25,21). The helical and C-terminal domains exhibit an even lower sequence identity than the rest of the protein, thereby prohibiting a direct identification of conserved regions through multiple pairwise alignment.…”
Section: Introductionmentioning
confidence: 99%